APPLICATION OF WIRELESSHART ADAPTOR FOR CONTROL VALVE ACTUATION - Jin Chien, Lim (2017)
Despite the advantages of industrial wireless standards such as WirelessHART, ISA100.11a and ZigBee, their application still faces a lot of challenges especially when it comes to interfacing with the real plant. This is due to lack of adequate infrastructure such as software and the interfacing circuitry to establish communication between the WirelessHART nodes and the actuators and sensors.